2015
DOI: 10.1108/imds-01-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

What catalyses mobile apps usage intention: an empirical analysis

Abstract: Purpose – Considering the lack of understanding of the mobile applications (mobile apps) market and low usage rates among Malaysians, Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) was adapted to investigate the determinants of consumer behavioural intention (BI) to use mobile apps. Design/methodology/approach – A total of 288 sample data was collected and analysed using partial least square equation modelling (PLS-SEM) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
254
4
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(345 citation statements)
references
References 69 publications
47
254
4
10
Order By: Relevance
“…Baptista and Oliveira (2015)'s research on the user acceptance of mobile banking discovered that hedonic motivation is an important variable corresponding to user acceptance. The same result was found in another study which investigated the user acceptance of mobile applications by Hew, Lee, Ooi and Wei (2015). The mobile applications which is accompanied with the element of fun and entertainment such as games, social network related are most welcomed by users.…”
Section: Hedonic Motivationsupporting
confidence: 76%
See 1 more Smart Citation
“…Baptista and Oliveira (2015)'s research on the user acceptance of mobile banking discovered that hedonic motivation is an important variable corresponding to user acceptance. The same result was found in another study which investigated the user acceptance of mobile applications by Hew, Lee, Ooi and Wei (2015). The mobile applications which is accompanied with the element of fun and entertainment such as games, social network related are most welcomed by users.…”
Section: Hedonic Motivationsupporting
confidence: 76%
“…The mobile applications which is accompanied with the element of fun and entertainment such as games, social network related are most welcomed by users. Users are highly affected by their feelings and emotions (Hew, Lee, Ooi and Wei, 2015). Thus, the following hypothesis is developed and tested in this study:…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…Further, similar results were reported by Leong, Hew, Tan, and Ooi (2013) and Lu and Su (2009) in case of adoption of online banking and mobile credit card and wireless mobile data services respectively. A study on mobile app usage intentions (Hew et al, 2015) has also confirmed a positive relationship between social influence and behavioural intentions. Thus, the following hypothesis is proposed:…”
Section: Social Influencementioning
confidence: 79%
“…Beberapa literatur yang melakukan studi tentang penerimaan teknologi telah menggunakan PLS [26], [28], [34]- [37]. PLS merupakan alat yang andal untuk menguji model prediksi karena memiliki beberapa keunggulan [31].…”
Section: Partial Least Squaresunclassified
“…Kebiasaan seseorang tersebut dapat direpresentasikan sebagai aspek habit [9]. Habit juga memiliki pengaruh yang positif terhadap behavioral intention dalam menggunakan suatu teknologi [7], [37]. Dengan demikian dapat dirumuskan hipotesis H7.…”
Section: H5 : Motivasi-motivasi Hedonis (Hedonic Motivation/hm)unclassified